PERANCANGAN UI/UX APLIKASI KAMUS BAHASA ISYARAT BERBASIS MOBILE DENGAN PENGUJIAN USABILITY MENGGUNAKAN SYSTEM USABILITY SCALE (SUS) - Agung Ukki Galih Cahyaningsih; Gede Aditya Pratama; Ni Wayan Yulya Wiani (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2026)
The development of mobile technology provides opportunities for creating more practical and interactive learning media, including sign language learning. However, the currently available sign language learning media are still limited and less effective, causing the general public to experience difficulties in understanding sign language. Based on observations and interviews conducted at several Special Schools (SLB), it was found that the sign language learning process still uses conventional methods such as guidebooks and direct practice between teachers and students. Therefore, this study aims to design the User Interface (UI) and User Experience (UX) of a mobile-based Sign Language. Dictionary application that is easy to use and capable of providing a good user experience. The methods used in this study are User Centered Design (UCD) for the UI/UX design process and System Usability Scale (SUS) for usability testing. Data collection was carried out through observation, interviews, and literature studies. The application prototype was designed using Figma with several main features such as vocabulary search, sign language categories, visual details of sign language movements, and a favorite feature. Usability testing was conducted on 10 respondents consisting of 5 teachers and 5 students from Special Schools (SLB). Based on the results of testing using the SUS method, the application obtained an average score of 90.25, which falls into the Excellent category and is included in the Acceptable level. These results indicate that the application has a very good usability level and is well accepted by users. Therefore, the designed mobile-based Sign Language Dictionary application is expected to become an effective and interactive learning medium and help improve communication between deaf individuals and the general public.